Distributional chaos for triangular maps - Babilonová, Marta (Annales Mathematicae Silesianae, 1999)
In this paper we show that triangular maps of the unit square can have properties that are impossible in the one-dimensional case. In particular, we find a map with infinite spectrum; a distributionally chaotic map whose principal measure of chaos is not generated by a pair of points and which has the empty spectrum; a distributionally chaotic map that is not chaotic in the sense of Li and Yorke.